COVID-19 barriers and response strategies for refugees and undocumented migrants in Turkey - Şevkat Bahar Özvarış; İlker Kayı; Deniz Mardin; Sibel Sakarya; Abdulkarim Ekzayez; Kristen Meagher; Preeti Patel (Elsevier, 2020)
Introduction: With more than 40 million confirmed cases of COVID-19 globally, the pandemic is continuing to severely challenge health systems around the world. Countries with high numbers of refugees face an additional burden on COVID-19 preventive and curative services made available and accessible to refugees. Turkey hosts the largest number of refugees globally, with a total of 4 million in 2020. Over 98% of refugees in Turkey reside in urban areas in large, crowded cities such as Istanbul, Gaziantep, and Hatay posing severe challenges for all health responses, including COVID-19. This study provides insights and analysis on the current situation for refugees, migrants under temporary protection and undocumented migrants in Turkey by focusing on the right to health and access to health care under pandemic conditions. Its main aim is to discuss the challenges and opportunities for COVID-19 responses relating to refugees, migrants under temporary protection and undocumented migrants in Turkey. Methods: This is a non- systematic and exploratory literature review from academic and grey sources. We reviewed published documents, meeting summaries, media reports/news and policy briefs in Turkish and English on the COVID-19 response in Turkey. Results: Since the start of the COVID-19 outbreak in Turkey, the Ministry of Health (MoH) has taken various steps to provide health care for all residents. However, several challenges arise when providing health care to refugees, migrants under temporary protection and other undocumented migrants including language barrier in accessing reliable information and access to health services for existing chronic conditions. Conclusion: While refugees, migrants under temporary protection and undocumented migrants have been granted access to services for COVID-19 related health problems, social and cultural barriers remain beyond the current legislation. Solidarity and whole-of-society inclusive approaches should always be the guiding principles in the COVID-19 response.